2015
DOI: 10.3201/eid2104.141479
|View full text |Cite
|
Sign up to set email alerts
|

Animal-Associated Exposure to Rabies Virus among Travelers, 1997–2012

Abstract: No demographic characteristics identified who might benefit most from pretravel counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 30 publications
3
25
1
2
Order By: Relevance
“…An estimated 31% of injuries requiring rabies PEP among international travelers are caused by NHPs, which rank second after dogs in most studies and first in studies conducted among travelers returning from Southeast Asia ( 2 ). In a recent GeoSentinel survey involving 2,697 travelers requiring rabies PEP, NHPs accounted for 66% of animal bites occurring in Southeast Asia, and tourists made up a disproportionately large portion of the NHP exposures (92%) ( 6 ). …”
Section: Discussionmentioning
confidence: 99%
“…An estimated 31% of injuries requiring rabies PEP among international travelers are caused by NHPs, which rank second after dogs in most studies and first in studies conducted among travelers returning from Southeast Asia ( 2 ). In a recent GeoSentinel survey involving 2,697 travelers requiring rabies PEP, NHPs accounted for 66% of animal bites occurring in Southeast Asia, and tourists made up a disproportionately large portion of the NHP exposures (92%) ( 6 ). …”
Section: Discussionmentioning
confidence: 99%
“…Animal bites are common in Nepal with risk of rabies exposure. [15][16][17] Pre-exposure rabies vaccine is desirable but not a must since effective post-exposure prophylaxis is available in the country. Cholera vaccine uptake was 34 (36%).…”
Section: Discussionmentioning
confidence: 99%
“…15 Many cases of rabies exposure have occurred early on in the travel period in the setting of short travel duration. 1,15 However, Dolan and colleagues reported that travellers seeking pretravel vaccination were more likely to be travelling for longer periods. 14 In our study, younger people were less likely to receive pre-exposure prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…The disease causes 60 000 deaths per year in the developing world but remains a rare diagnosis in travellers. 1 However, travellers frequently seek medical advice for animal bites or scratches, sometimes requiring rabies postexposure prophylaxis, which disrupts travel plans. 2 Pre-exposure prophylaxis greatly facilitates postexposure prophylaxis measures.…”
mentioning
confidence: 99%